Pregnancy per AI after presynchronizing estrous cycles with Presynch-10 or PG-3-g before Ovsynch-56 in four dairy herds of lactating dairy cows - Stevenson, Jeffrey S.; Pulley, Stephanie Leeann (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2014)
The objective was to determine the effect of 2 presynchronization treatments on first-service pregnancy rate in 4 dairy herds during warm and cool seasons of the year. Cows with ear tags ending with even digits at calving were enrolled in Presynch-10 with 2, 25-mg injections of prostaglandin F2α (i.e., PG-1 and PG-2) 14 days apart. Cows with ear tags ending with odd digits were enrolled in PG-3-G comprising 1, 25-mg injection of PG (Pre-PG) 3 days before 100 μg gonadotropin-releasing hormone (Pre-GnRH), with the Pre-PG injection administered at the same time as PG-2 in the Presynch-10 treatment in the Presynch-10 treatment. Ten days after PG-2 or Pre-PG, all cows were enrolled in a timed artificial insemination (TAI) protocol (Ovsynch-56; injection of GnRH 7 days before [GnRH-1] and 56 hours after [GnRH-2] PG with AI 16 to 18 hours after GnRH-2). Median days in milk (DIM) at scheduled TAI were 75 days, which did not differ among herds. Cows detected in estrus before the scheduled TAI were inseminated early (early bred; EB). Pregnancy was diagnosed at days 32 to 38 and at days 60 to 66 after TAI by transrectal ultrasonography or transrectal palpation. Data were analyzed with herd as a random effect and with fixed effects of treatment (EB, Presynch-10, PG-3-G), parity (primiparous vs. multiparous), season (hot [June through September] vs. cool-cold [October through May]), DIM, estrus at TAI (0 vs. 1), and all 2-way interactions with treatment. The pregnancy rate at days 32 to 38 for EB (n = 472), Presynch-10 (n = 1,247), and PG-3-G (n = 1,286) were 31.4, 35.0, and 41.2%, respectively; pregnancy rate at days 60 to 66 was 29.8, 32.2, and 37.3%, respectively. Season significantly influenced pregnancy rate at days 32 to 38 and days 60 to 66, but a treatment by season interaction was not detected. The pregnancy rate for PG-3-G and Presynch-10 treatments did not differ during cool-cold weather (d 32 to 38: 46.8 vs. 44.3%; days 60 to 66: 41.6 vs. 41.1%, respectively), but PG-3-G and Presynch-10 produced a higher pregnancy rate than EB at days 32 to 38. During summer, pregnancy rate in PG-3-G was greater than in Presynch-10 (days 32 to 38: 35.9 vs. 26.7% or days 60 to 66: 33.2 vs. 24.4%, respectively), and pregnancy rate in EB cows did not differ from that of Presynch-10 cows. Although pregnancy loss did not differ for EB, Presynch-10, and PG-3-G treatments (4.0, 6.7, and 9.3%, respectively), pregnancy loss from days 32 to 38 and days 60 to 66 was 2-fold greater in thinner cows (<2.5 vs. ≥2.5; 9.0 vs. 4.4%). We concluded that presynchronizing estrous cycles with PG-3-G produced more pregnancies than inseminating cows at estrus during cooler weather and was superior to Presynch-10 during summer.
Dairy Research, 2012 is known as Dairy Day, 2012
Keywords: Dairy cows; Presynch-10; PG-3-G; Pregnancy rate; Artificial insemination